Understanding leadership challenges faced by humanitarian aid workers: insights from the experiences of NNPHL training participants - Godfred Nyarko; Ariana Marnicio; Vincenzo Bollettino (Journal of International Humanitarian Action)
Abstract This paper examines the self-reported leadership challenges experienced by humanitarian aid workers who participated in the National NGO Program on Humanitarian Leadership (NNPHL) Program. Data were drawn from NNPHL program participants describing leadership challenges they faced in their humanitarian work. Responses were analyzed qualitatively revealing 10 broad themes of leadership challenges: (1) organizational capacity and resource constraints, (2) managerial decision-making styles, (3) bureaucracy and external influence, (4) purpose, motivation, and influence, (5) coordination and cooperation, (6) trust and cohesion within teams, (7) staff well-being and burnout, (8) identity and diversity, (9) self-efficacy and confidence, (10) security. These findings were then situated in the broader literature on challenges identified in humanitarian aid contexts. Humanitarian aid workers offer valuable first-hand insights into the leadership challenges they face in their work. Understanding leadership challenges from the perspective of aid workers provides valuable insight that can be used to inform decision-making and policy development within humanitarian organizations. The findings can also help inform and shape the development of humanitarian training programs by tailoring humanitarian education curricula to address the challenges encountered by aid workers themselves.